Gross Job-Creation and Gross Job-Destruction Determinants: Empirical Analyse at Micro Firms Data Level - T. Leonardo; D. Francisco (Ekonomika Nauki)
This study analyses gross job-creation and gross job-destruction determinants at the firm level for a panel of Portuguese micro-firms across four industry sectors, using the Ordinary Leat Square and Fixed Effect econometrics model to analyse a database consisting on 15.686 micro firms, for the period going from 2010 to 2017. It was found that laggard gross job-creation, assets tangibility, financial leverage, profits, and the fact firms belong to the construction sector determine gross job-creation. Regarding gross job-destruction, it was found that this variable is determined by its laggard variable, firm’s size, worker’s tenure, and the fact the firm belongs to the hotels and restaurant sector. Finally, findings suggest that a resource-based approach explains gross job-creation and gross job-creation for micro firms by using microdata. This study contributes to the state of the art on the determinants of employment and firing at micro firms’ level as it investigates the importance of the independent variables in explaining micro firm’s labour demand in Portugal.